UNC93B1 Is Widely Expressed in the Murine CNS and Is Required for Neuroinflammation and Neuronal Injury Induced by MicroRNA let-7b - Klammer, Markus G.; Dzaye, Omar; Wallach, Thomas; Krüger, Christina; Gaessler, Dorothea; Buonfiglioli, Alice; Derkow, Katja; Kettenmann, Helmut; Brinkmann, Melanie M.; Lehnardt, Seija (Frontiers in Immunology, 2021)
The chaperone protein Unc-93 homolog B1 (UNC93B1) regulates internalization, trafficking, and stabilization of nucleic acid-sensing Toll-like receptors (TLR) in peripheral immune cells. We sought to determine UNC93B1 expression and its functional relevance in inflammatory and injurious processes in the central nervous system (CNS). We found that UNC93B1 is expressed in various CNS cells including microglia, astrocytes, oligodendrocytes, and neurons, as assessed by PCR, immunocyto-/histochemistry, and flow cytometry. UNC93B1 expression in the murine brain increased during development. Exposure to the microRNA let-7b, a recently discovered endogenous TLR7 activator, but also to TLR3 and TLR4 agonists, led to increased UNC93B1 expression in microglia and neurons. Microglial activation by extracellular let-7b required functional UNC93B1, as assessed by TNF ELISA. Neuronal injury induced by extracellular let-7b was dependent on UNC93B1, as UNC93B1-deficient neurons were unaffected by the microRNA’s neurotoxicity in vitro. Intrathecal application of let-7b triggered neurodegeneration in wild-type mice, whereas mice deficient for UNC93B1 were protected against injurious effects on neurons and axons. In summary, our data demonstrate broad UNC93B1 expression in the murine brain and establish this chaperone as a modulator of neuroinflammation and neuronal injury triggered by extracellular microRNA and subsequent induction of TLR signaling.